RESULTS OF NEOADJUVANT CHEMOTHERAPY TREATMENT FOR HER2(+) BREAST CANCER USING A COMBINATION CHEMOTHERAPY REGIMEN WITH HER2 INHIBITORS AT NGHE AN ONCOLOGY HOSPITAL. (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the response to neoadjuvant therapy with combining chemotherapy and anti-HER2 therapy for patients with stage II–III, HER2-positive breast cancer at Nghe An Oncology Hospital.Methods: This retrospective–prospective descriptive study included 65 patients with stage II–III, HER2-positive breast cancer who received neoadjuvant chemotherapy with either the AC-TH, TCH, AC-THP or TCHP regimen at the Department of Internal Medicine 4, Nghe An Oncology Hospital, from June 2023 to June 2026.Results: Some common characteristics of the patient group: The age group from 40-60 is the most common, accounting for 67.2%. The positive and negative hormone receptor rates are 46.2% and 53.8%, respectively. 84.6% of patients use chemotherapy combined with trastuzumab, while 15.4% use chemotherapy combined with the trastuzumab + pertuzumab doublet. The percentages of the treatment regimens chosen are as follows: AC-TH at 47.7%, TCH at 36.9%, AC-THP at 6.2%, and TCHP at 9.2%.     Conclusions: Neoadjuvant chemotherapy combined with anti-HER2 agents yields high rates of total pathological complete response (tpCR) and is well-tolerated in patients presenting with HER2-overexpressing locally advanced and early-stage breast cancer. The majority of patients achieve favorable clinical and histopathological responses. The addition of anti-HER2 agents—particularly dual anti-HER2 blockade—enhances treatment efficacy.
Keywords: Breast cancer, neoadjuvant therapy, AC-TH, TCH, AC-THP, TCHP